Exploring clinical features of children with autism in Bogura city of Bangladesh (Dhaka University Journal of Biological Sciences, 2024)
Autism is marked by a dense shortage of social, language, and cognitive abilities. To become aware and start earlier treatment, these criteria needed to be known from their cultural context, helpful for the betterment of children with autism and their caregivers. The study aimed to explore the severity of six clinical features (e.g., socio-emotional, language, behavioral, affective, cognitive, and physical symptoms) of Bangladeshi children with autism according to the DSM-V. Thirty six parents (55.56% mother and mean age = 33.75 years) of autistic children participated as respondents. Required data were collected using a personal information form and the Bangla version of the Clinical Features of Autistic Children Questionnaire. Data were analyzed through frequency, percentage, and correlation. The results showed that the severity of social and physical developmental symptoms was comparatively lower, while language, behavioral, affective, and cognitive developmental symptoms were comparatively higher among children with autism. In addition, no significant correlation was found among socio-emotional, language, behavioral, affective, cognitive, and physical symptoms in terms of parents’ educational qualifications and family income of children with autism. The study recommends that the concerned authorities should immediately focus on the more severe clinical features and affecting factors for the betterment of both children with autism and their caregivers.Dhaka Univ. J. Biol. Sci. 33(1): 67-77, 2024 (January)